Sifat Fisik Farmaseutik Tablet Hisap Herbal Yang Menggunakan PVP K-30 Dan Gom Arab Sebagai Pengikat - Haris, Zulfiah; Mirawati, Mirawati; Nurlina, Nurlina (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Tablets are pharmaceutical preparations that are most widely used by the public compared to other pharmaceutical preparations. One type of tablet is lozenges which are solid preparations containing one or more medicinal ingredients, generally with flavorful and sweet ingredients, which can make the tablet dissolve or disintegrate slowly in the mouth. Polyvinyl pyrylone K-30 (PVP K-30) binder has an advantage over other binders, as it can increase the hardness of tablets, making tablets a compact preparation. Arabic gum also has good flow properties, pharmacologically inert, has good compressibility and compactness. The purpose of the review is to determine the pharmaceutical properties of herbal lozenges that use PVP K-30 and Arabic gum as binders. The method used in reviewing this review is an electronic literature study by accessing journal search sites related to the keyword " PVP K-30 lozenges and gum arabic lozenges". Binder material as one of the ingredients needed in lozenges because the binder can determine the level of hardness, brittleness and destruction time of lozenges. PVP binders and gum arabic are examples of binders that have good flow properties and stationary angles, and for hardness PVP tablets are good binders, but if the concentration used is high then the brittleness level is reduced.